2022
DOI: 10.1001/jama.2022.11966
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dual Antiplatelet Therapy With Ticagrelor With Vein Graft Failure After Coronary Artery Bypass Graft Surgery

Abstract: IMPORTANCEThe role of ticagrelor with or without aspirin after coronary artery bypass graft surgery remains unclear.OBJECTIVE To compare the risks of vein graft failure and bleeding associated with ticagrelor dual antiplatelet therapy (DAPT) or ticagrelor monotherapy vs aspirin among patients undergoing coronary artery bypass graft surgery.DATA SOURCES MEDLINE, Embase, and Cochrane Library databases from inception to June 1, 2022, without language restriction. STUDY SELECTION Randomized clinical trials (RCTs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 23 publications
1
30
1
Order By: Relevance
“…Third, the fate of the previously implanted stents and atherosclerosis of native arteries might have been affected by the preoperative withdrawal of antiplatelet drugs and anticoagulants. Similarly, antithrombotic therapy might have had an impact on thrombotic events, early and late, after surgery [ 14 ]. However, collinearity between the use of antithrombotic drugs and prior PCIs prevents a reliable analysis of the impact of using these drugs on the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the fate of the previously implanted stents and atherosclerosis of native arteries might have been affected by the preoperative withdrawal of antiplatelet drugs and anticoagulants. Similarly, antithrombotic therapy might have had an impact on thrombotic events, early and late, after surgery [ 14 ]. However, collinearity between the use of antithrombotic drugs and prior PCIs prevents a reliable analysis of the impact of using these drugs on the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…First, this study did not report statistical heterogeneity . Assessing heterogeneity is important in meta-analyses using individual patient data and those using aggregated data, particularly when the confidence intervals of effect estimates of individual studies do not overlap well.…”
mentioning
confidence: 94%
“…To the Editor We have several concerns about the recent systematic review and meta-analysis that found ticagrelor and aspirin vs aspirin alone reduced the risk of saphenous vein graft failure after coronary artery bypass graft surgery.…”
mentioning
confidence: 99%
“…A 1993 meta‐analysis of seven RCTs including 1443 patients showed that the use of aspirin after CABG was associated with a lower risk of SVG occlusion 6 . A recent meta‐analysis involving 1316 patients and 1668 SVG showed that adding ticagrelor to aspirin was associated with a significantly lower incidence of SVG failure (11.2%) per graft than was aspirin (20%; difference, −8.7% [95% confidence interval, CI, −13.5% to −3.9%]; OR, 0.51 [95% CI, 0.35–0.74]; p < .001) 7 . Aggressive lipid‐lowering reduced progression of atherosclerosis in grafts in the post‐CABG trial 8 .…”
mentioning
confidence: 99%
“… 6 A recent meta‐analysis involving 1316 patients and 1668 SVG showed that adding ticagrelor to aspirin was associated with a significantly lower incidence of SVG failure (11.2%) per graft than was aspirin (20%; difference, −8.7% [95% confidence interval, CI, −13.5% to −3.9%]; OR, 0.51 [95% CI, 0.35–0.74]; p < .001). 7 Aggressive lipid‐lowering reduced progression of atherosclerosis in grafts in the post‐CABG trial. 8 In addition, higher low‐density lipoprotein (LDL) levels during the first postoperative year were associated with significantly greater VGD 3 years after CABG in the aggressive cholesterol therapy to inhibit vein graft events trial.…”
mentioning
confidence: 99%